Characterisation of CrN-NbN Superlattice Coatings, including their simulated wear debris, for total joint prosthesis bearing surface applications - Smith, Conor (2023)
Total joint replacements have historically favoured a hard material for the femoral head with Ultra high molecular weight polyethylene (UHMWPE) as the material for the acetabular cup. There has recently been more interest in metal on metal (MoM) and ceramic on ceramic (CoC) pairings for total joint replacements influenced by a desire to reduce the volumes of wear debris produced by these systems as MoM and CoC pairings have generally been shown to have lower wear rates than those with a UHMWPE acetabular cup, with <0.1mm3 per million cycles for ceramic on ceramic, 1.23±0.5mm3 per million cycles for metal on metal and 13mm3 per million cycles for metal on UHMWPE [1] [2] [3]. In work previously conducted by Zimmer Biomet the chromium nitride – niobium nitride (CrN-NbN) superlattice coating produced by high power impulse magnetron sputtering (HIPIMS) was identified as having significant potential yet little was known about the influence of these wear particles to influence late aseptic loosening. This coating method had already been shown to produce coatings with improved density, adhesion, surface roughness and through a HIPIMS deposition route a claimed greater control over composition, microstructure and mechanical properties of the coating produced. Such coatings are usually highly resistant to wear when compared with other materials used for articulating surfaces of joint replacements, making them of significant interest for articulating surfaces. While this potentially leads to a joint replacement surface that produces less wear debris and has improved device lifespans it is important to investigate first in vitro then in vivo what influence such wear particles may have in terms of cytocompatibility and tissue response. The work presented here aims to characterize the CrN-NbN coating and generated particles from that coating. The biological characterisation of the particles is of particular interest in determining the potential for osteolysis. Characterisation of the CrN-NbN superlattice coating demonstrated droplets, pits, and seams as surface features of the coating and in the case of the droplets may be a source of wear particles. The CrN-NbN superlattice coating was shown to have a surface layer of NbN that was oxidised and an underlying layer of CrN that was partially oxidised and appears to create a passivating layer. The layer thickness of the CrN-NbN superlattice was found to be approximately 6nm for both the CrN and NbN layers. Simulated wear debris was produced through a thermal shock method using CrN-NbN superlattice coated knee implants produced by Zimmer Biomet. Characterisation of the CrN-NbN wear particles showed a mixture of granular and columnar particles below 10 µm in size, generally smaller particles appeared to be more granular while larger particles appeared to be columnar. Then the potential for late aseptic loosening was investigated through analysis of the release of inflammatory cytokines by macrophages and osteoblasts in response to the coating and particles produced from the coating and compared with other commonly used implant materials. The CrN-NbN superlattice coating surface by itself was not shown to produce higher levels of inflammatory cytokines when compared to other common implant materials such as titanium nitride or cobalt chrome in macrophages or osteoblasts. However, the particles produced from the CrN-NbN superlattice coating did however show significantly higher levels of IL-6 release in macrophages when compared to titanium nitride and alumina, with an average increased release of 914.6 pg/ml and 999 pg/ml over 7 days respectively. The particles produced from the CrN-NbN superlattice coating also showed significantly higher levels of TNF-α release when compared to titanium nitride and alumina, with an average increased release of 543.4 pg/ml and 542.2 pg/ml over 7 days respectively. Particles produced from the CrN-NbN superlattice coating did not show a significant increase in IL-6 release from osteoblasts initially, it then however showed a significant increase when compared to titanium nitride at day 3 and when compared to alumina at day 14. The release of IL-6 was not significantly increased when compared to tissue culture plastic, however. The average increase in release of IL-6 for osteoblasts exposed to titanium nitride and alumina was 1314.8 pg/ml and 544.0 pg/ml respectively. While these results would indicate that the potential for osteolysis and late aseptic loosening is higher in the CrN-NbN superlattice coating when compared with other available materials. This increase may be as a result of differing particle sizes, as the comparison materials are 3 µm in size while the CrN-NbN superlattice particles are in the range of <10 µm. It is however important to note that these are the results when comparing identical particle concentrations. As the material is expected to have a significantly lower wear rate when compared to other commonly used materials this may mitigate the higher release of inflammatory cytokines. An approximation of cytokine release in response to the CrN-NbN superlattice particles at expected concentrations from wear simulations, based on the results found in this research, indicate a higher TNF-α release and lower IL-6 release when compared to other commonly used materials. This should however be investigated as part of a larger study.